IMPLEMENTATION OF INVENTORY ACCOUNTING INFORMATION SYSTEMS AT PHARMACY (Case Study at Tirta Pharmacy) - Mustofa, Ahmad; Ekasari, Kurnia; Kusmintarti, Anik (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this research is to provide an overview of the systems and procedures for cash receipts and disbursements associated with merchandise inventory. This research was a qualitative study to describe the business flow of incoming and outgoing items by looking at the accounting information system design. The object of this research was Tirta Pharmacy located in Jember Regency, East Java. The type of data in this study was primary data in the form of observations and interviews with pharmacists in Tirta pharmacy. Data analysis was carried out in this study in order to analyze obstacles and problems regarding financial reports, the functions of the data obtained, and procedures related to the design of accounting information systems with the aim of implementing a good financial statement accounting information system and can improve efficiency and stabilization of operational activities, especially in the drug supply division at Tirta Pharmacy.. The results of this study propose systems and procedures for cash receipts and disbursements, as well as suggestions for using information technology in carrying out company operational activities.